MANAJEMEN SARANA PRASARANA DALAM MENINGKATKAN PROSES PEMBELAJARAN - Aditya Nugraha; Happy Fitria (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The purpose of this study was to determine the completeness of the infrastructure, the management of infrastructure and the efforts made by Palembang State Senior High School in improving the learning process. In this study the research data used a type of qualitative research, in this study the data was used using analysis gaps that helped Palembang State High School 9 in revealing which ones should be improved in improving infrastructure at Palembang State High School 9. Gap analysis includes determination, documentation, and the positive side of diversity of desires and capabilities now. The results of the gap analysis show that 14 items have not met the standards contained in Permen No. 24 of 2007, facilities that do not meet the standards include: Classrooms, library rooms, biological laboratory rooms, physics laboratory rooms, chemical laboratory rooms, computer laboratory rooms, spaces language laboratory, teacher's room, UKS room, student organization room, toilet, warehouse, circulation room, and sports equipment room. Whereas facilities that are in accordance with the standards contained in Permen No. 24 of 2007 are only 4 items including: leadership room, administration room, worship room, and counseling room. The principal as the school leader has implemented an administrative function to fix the existing infrastructure in the school starting from the functions of planning, coordinating, channeling, to accountability, by setting these functions expected to optimize infrastructure in improving the learning process at Palembang 9 Public High School.